2018
DOI: 10.1038/s41598-018-32416-z
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-based Chemiluminescence for Chiral Discrimination of Thiol-Containing Amino Acids

Abstract: The ability to recognize the molecular chirality of enantiomers is extremely important owing to their critical role in drug development and biochemistry. Convenient discrimination of enantiomers has remained a challenge due to lack of unsophisticated methods. In this work, we have reported a simple strategy for chiral recognition of thiol-containing amino acids including penicillamine (PA), and cysteine (Cys). We have successfully designed a nanoparticle-based chemiluminescence (CL) system based on the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…A large number of analytical methods, including liquid‐phase separation, [ 10 ] mass spectrometric techniques, [ 11 ] gas chromatography, [ 12 ] capillary electrophoresis, [ 13 ] and nuclear magnetic resonance protocols [ 14 ] have been used for enantiomer discrimination. [ 11,15 ] However, most of these conventional techniques suffer from unavoidable disadvantages such as complex experimental setup, long‐time sample pretreatment, expensive chiral stationary phases or chiral selectors. Fortunately, the chirality of biomolecules can manifest itself optically, which has made optical spectroscopic measurements of molecular chiral–optical (chiroptical) effects attractive as they provide label‐free, noninvasive and cost‐efficient characterizations.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of analytical methods, including liquid‐phase separation, [ 10 ] mass spectrometric techniques, [ 11 ] gas chromatography, [ 12 ] capillary electrophoresis, [ 13 ] and nuclear magnetic resonance protocols [ 14 ] have been used for enantiomer discrimination. [ 11,15 ] However, most of these conventional techniques suffer from unavoidable disadvantages such as complex experimental setup, long‐time sample pretreatment, expensive chiral stationary phases or chiral selectors. Fortunately, the chirality of biomolecules can manifest itself optically, which has made optical spectroscopic measurements of molecular chiral–optical (chiroptical) effects attractive as they provide label‐free, noninvasive and cost‐efficient characterizations.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrate that CCL can distinguish some chiral host–guest systems, which would be difficult for NMR and fluorescence spectroscopy. Compared with the method for chiral discrimination using a QD enhanced-CL system, 41 the commercial chiral metal–organic complexes used in the present work are easily available. In addition, they allow facile discrimination between a wide range of enantiomeric pairs.…”
Section: Resultsmentioning
confidence: 99%
“…NP-based enantiomeric recognition and separation have been widely discussed and studied in the past decade. Studies reported chiral -modified nanomaterials for catalysis [70,71], chiral drug separation [71] and sensing [54,55,56,57,58,59,60,63,68,72,73,74]. In this section, we will focus on the enantiomeric recognition and the fabrication of most commonly used gold and silver materials for chiral NPs.…”
Section: Enantiomeric Recognition By Chiral Nanoparticlesmentioning
confidence: 99%
“…The working principle is that interactions with specific enantiomers occur on the surface of metal NPs, which means that interactions can be monitored according to changes in surface plasmon resonance (SPR). Furthermore, chiral ligand-capped quantum dots (QDs) have also received considerable attention in this field, due to the size-dependent optical properties, bright chemiluminescence, and excellent chemical stability [63,64,65]. Beside the applications of magnetic nanoparticles (MNPs) such as catalysts, targeted administration and magnetic resonance imaging (MRI) [66,67], researchers have even capped the surfaces of MNPs with chiral ligands to promote specific interactions with the target enantiomers.…”
Section: Introductionmentioning
confidence: 99%